Criminal Law Settlement Through Restorative Justice in Indonesia in Terms of Justice and Legal Certainty - Mega Jaya, Arizon; Mega Jaya, Aristama (International Asia Of Law and Money Laundering (IAML), 2024)
The win lose solution nature of the criminal justice process often leads to disappointment. In addition, the judicial process, which is expected to be a formal way, turns out to be expensive, prolonged, tiring and sometimes does not solve the problem. From this phenomenon, efforts to reform the national criminal law are needed, one of which is the concept of "restorative justice". Therefore, the purpose of this research is to explain and analyse how Restorative Justice is resolved and to examine whether Restorative Justice has fulfilled the principles of justice and legal certainty. The research method used is normative juridical. The results of this study are Restorative Justice is carried out by means of a mediation and dialogue process by including victims, perpetrators, families of perpetrators / victims and other parties involved can work together to create an agreement for a fair and balanced settlement of the case for both parties whose purpose is to restore the situation to its original state and restore patterns of good relations in society. The implementation of case settlement through restorative justice as an alternative settlement of certain cases is in accordance with the purpose of the law itself, namely to fulfil the principles of justice and legal certainty.